2015
DOI: 10.1080/10400435.2015.1074631
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of powered wheelchair provision in Italy

Abstract: Powered wheelchairs are complex and expensive assistive devices that must be selected and configured on the basis of individual user needs, lifestyle, motivation, driving ability, and environment. Providing agencies often require evidence that their financial investment will lead to a successful outcome. The authors surveyed a sample of 79 users who had obtained powered wheelchairs from a Regional Health Service in Italy in the period 2008-2013. Follow-up interviews were conducted at the users' homes in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…PIADS proved to have good psychometric properties [ 21 ], which were confirmed in its Italian version, being able to detect the psychosocial impact of different assistive devices [ 22 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…PIADS proved to have good psychometric properties [ 21 ], which were confirmed in its Italian version, being able to detect the psychosocial impact of different assistive devices [ 22 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have also explored powered wheelchair users' experiences. Recent quantitative and qualitative research with adult users described powered wheelchairs as a mixed blessing in terms of usability, safety, cost, accessibility and stigma (Blach Rossen et al, 2012;Pettersson et al, 2015;Torkia et al, 2015;Salatino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors reported on QoL using examples of participant's enhanced occupational performance. Respondents noted that the PMD had a great impact on their QoL citing this as a positive result of using the PMD (Carver et al, 2016;Corazon et al, 2019;Edwards and McCluskey, 2010;Evans, 2000;Fomiatti et al, 2014;Fredriksson et al, 2020;May and Rugg, 2010;Pettersson et al, 2016;Salatino et al, 2016;Samuelsson and Wressle, 2014;Sullivan et al, 2020;Zagol and Krasuski, 2010).…”
Section: Enhanced Quality Of Lifementioning
confidence: 99%
“…The Personal Independence Profile (PIP) Perr (2014) x X Self-report measure of psychological and environmental aspects of independence. 3 subscales (perceived control over one's self, psychological self-reliance and physical functioning Psychosocial Impact of Assistive Devices Scale (PIADS) Francisco et al (2019), Giesbrecht et al (2009), Salatino et al (2016) x 26 item self-report to assess psychosocial impact of assistive device on functional independence, wellbeing and QoL Quebec User Evaluation of Satisfaction with assistive Technology (Quest 2.0) Giesbrecht et al (2009), Jedeloo et al (2002) PMD is reported in 10 studies as specifically enabling participation in shopping, and mobilising in the community (Brandt et al, 2004;Evans, 2000;Fredriksson et al, 2020;Hoenig et al, 2007;Labbé et al, 2020;Löfqvist et al, 2012;May and Rugg, 2010;Pettersson et al, 2015Pettersson et al, , 2016Sullivan et al, 2020). reported on 66 participants who identified that their PMD was used 3-5 times per week for activities that included shopping, visiting friends, keeping appointments and mobilising in the community.…”
Section: Clients Perceived Participationmentioning
confidence: 99%